2017
DOI: 10.3390/ijerph14040446
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of the Influence of Sport and Educational Factors on the Prevalence and Initiation of Smoking in Older Adolescents from Croatia

Abstract: The prevalence of smoking among Croatian adolescents is alarmingly high, but no previous study has prospectively examined the sport- and academic-factors associated with smoking and smoking initiation. This study aimed to prospectively examine the associations between scholastic (educational) achievement and sport factors and smoking in 16- to 18-year-old adolescents. This two-year prospective cohort study included 644 adolescents who were 16 years of age at baseline (46% females). Baseline testing was impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
(89 reference statements)
3
14
2
Order By: Relevance
“…Briefly, Zenic et al reported a two-fold increase in harmful drinking in both adolescent boys and girls over a two-year period [9]. On the other hand, another study reported a much lower increase in smoking prevalence over two years in adolescent boys than in girls (girls: 37% to 49%; boys 44% to 48%) [31]. Our results, however, emphasized another interesting conclusion.…”
Section: Prevalence and Dynamics Of Changes In Cshd In Adolescencesupporting
confidence: 38%
See 4 more Smart Citations
“…Briefly, Zenic et al reported a two-fold increase in harmful drinking in both adolescent boys and girls over a two-year period [9]. On the other hand, another study reported a much lower increase in smoking prevalence over two years in adolescent boys than in girls (girls: 37% to 49%; boys 44% to 48%) [31]. Our results, however, emphasized another interesting conclusion.…”
Section: Prevalence and Dynamics Of Changes In Cshd In Adolescencesupporting
confidence: 38%
“…Although we could not find any study performed in southeastern Europe where trends in changes in CSHD were reported, we may say that the increase in the prevalence of CSHD prevalence that we found for those between 16 and 18 years of age in this period was expected. Namely, recent studies in the former Yugoslavia reported a significant increase in the smoking prevalence in Bosnian-Herzegovinian and Croatian adolescents over a two-year period (from 40% to 47% ever smokers) and from 28% to 36% (daily smokers) for Croatian and Bosnian-Herzegovinian adolescents, respectively) [10,31]. In addition, a significant increase in drinking prevalence was recorded by the AUDIT score in adolescents from Bosnia and Herzegovina for the same age [9].…”
Section: Prevalence and Dynamics Of Changes In Cshd In Adolescencementioning
confidence: 94%
See 3 more Smart Citations